Study on the extraction process and optical properties of mangosteen pericarp for Dye Sensitized Solar Cell (DSSC) application / M. A. S. Suri ... [et al.] - S. Suri, M. A.; Yahaya, N. A.; Hamzah, K. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Dye Sensitized Solar Cell (DSSC) is the third generation of photovoltaic solar cell that provides an alternative concept of organic or inorganic components in photovoltaic solar cells. The use of natural pigments as sensitizers from organic gives the advantages as it is easy to obtain, low cost and environmentally friendly compared to the inorganic components of this alternative form of solar energy conversion. There are many natural dye extracts that can be used as photosensitizer such as from flowers, fruits, leaf plant etc. which results vary for solar to electric conversion efficiencies. One of the good candidates for the dye used in DSSC is mangosteen pericarp which is expected to contribute to the high light absorption. This is because high light absorption would give high efficiency in DSSC. Therefore in this study, the investigation on the extraction process of the mangosteen pericarp was studied and compared. The preparation of the natural dye by extraction affected the conversion efficiency. The optical properties of mangosteen pericarp dye were also evaluated as high absorption leads to high efficiency of solar cell. The absorption spectrum of mangosteen pericarp dye with acetone extraction gave higher maximum wavelength that ranged between 200 - 490 nm. The DSSC sensitized by mangosteen pericarp dye with acetone also had higher current flow and voltage which are 0.027 mA and 1.6 mV respectively.